Tunable Schottky barrier height of ZnO films by Cu doping. Issue 1 (July 2020) - Nurfani, E; Kesuma, W A P; Lailani, A; Anrokhi, M S; Kadja, G T M; Rozana, M; Sipahutar, W S; Arif, M F
Abstract: Understanding a mechanism behind photosensitivity in oxide materials is important to realize future photodetector devices. We have studied electrical properties of ZnO:Cu (0-2.5 at.%) films deposited by a spray technique. Here, Ag-ZnO-Ag planar configuration was used to study the Schottky barrier. Using current-voltage (I-V) characterization, a significant increment in the photocurrent is observed in all samples, indicating a photosensitivity behavior. The Schottky barrier is clearly observed in the doped sample. The Cu concentration of 1.5 at.% show the highest Schottky barrier height (0.8 eV), which may be originated from carrier trapping under dark and carrier de-trapping under ultraviolet radiation. Thus, our result is essential to improve the functionality of ZnO for photodetector applications.